2016
DOI: 10.1186/s13075-016-1142-7
|View full text |Cite
|
Sign up to set email alerts
|

Power Doppler ultrasonographic assessment of the joint-draining lymph node complex in rheumatoid arthritis: a prospective, proof-of-concept study on treatment with tumor necrosis factor inhibitors

Abstract: BackgroundEmerging research on the mechanisms of disease chronicity in experimental arthritis has included a new focus on the draining lymph node (LN). Here, we combined clinical-serological analyses and power Doppler ultrasound (PDUS) imaging to delineate noninvasively the reciprocal relationship in vivo between the joint and the draining LN in patients with rheumatoid arthritis (RA).MethodsForty consecutive patients refractory to conventional synthetic disease-modifying anti-rheumatic drugs were examined thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
(48 reference statements)
0
14
0
1
Order By: Relevance
“…These pathologic collapse mechanisms are notably distinct from reductions in lymph node volume associated with resolution of inflammation, where T-cells exhibit anti-lymphangiogenic properties to regress the expanded lymph nodes towards baseline 18 , 19 . Importantly, similar dynamic lymph node changes suggestive of pathologic collapse have also been shown in clinical correlate studies of patients with rheumatoid arthritis 20 , 21 Detailed ex vivo analysis of PLV contractile function in TNF-Tg mice indicated that deficits in PLV contractility precede the pathogenic processes involved in PLN collapse, and thus may be a driving factor in disease pathogenesis and the onset of severe arthritis 8 . Mechanistically, the B-cell translocation and PLN clogging is thought to be related to stagnation of intra-sinus CXCL13 + macrophages from loss of lymphatic contractility 2 , and these cellular processes remain an active area of investigation.…”
Section: Introductionmentioning
confidence: 65%
“…These pathologic collapse mechanisms are notably distinct from reductions in lymph node volume associated with resolution of inflammation, where T-cells exhibit anti-lymphangiogenic properties to regress the expanded lymph nodes towards baseline 18 , 19 . Importantly, similar dynamic lymph node changes suggestive of pathologic collapse have also been shown in clinical correlate studies of patients with rheumatoid arthritis 20 , 21 Detailed ex vivo analysis of PLV contractile function in TNF-Tg mice indicated that deficits in PLV contractility precede the pathogenic processes involved in PLN collapse, and thus may be a driving factor in disease pathogenesis and the onset of severe arthritis 8 . Mechanistically, the B-cell translocation and PLN clogging is thought to be related to stagnation of intra-sinus CXCL13 + macrophages from loss of lymphatic contractility 2 , and these cellular processes remain an active area of investigation.…”
Section: Introductionmentioning
confidence: 65%
“…Moreover, PDUS signal was amplified in the cortical and hilar regions of lymph nodes at baseline but returned to normal levels after 3 months of anti-TNF and/or methotrexate therapy 98 . In a follow-up study of 40 consecutive patients with RA refractory to treatment with DMARDs and 20 healthy individuals, 97 PDUS demonstrated considerable alterations of RA lymph node morphology and volume following anti-TNF treatment, and a degree of concordance of these alterations with synovitis activity in peripheral joints. Interestingly, low PDUS signal in the lymph nodes (which has also been observed in collapsed murine lymph nodes) 70,72 at baseline was strongly associated with a poor clinical response to anti-TNF therapy.…”
Section: Lymphatic Phenotypes In Ramentioning
confidence: 99%
“…Preliminary work with indocyanine green near-infrared (ICG-NIR) fluorescence imaging has been promising in providing sensitive, real-time non-invasive means to evaluate the layout and function of the lymphatic vasculature ( 31 , 38 , 39 ), and the first study of lymphatic flow in RA patients with this modality is currently being performed (ClinicalTrials.gov NCT02680067). Meanwhile, the change in size of the local draining lymph nodes has been shown to reflect joint inflammatory activity, as well as response to therapy ( 40 ). Even prior to clinical lymphadenopathy, evaluation of draining lymph nodes of inflamed joints by power Doppler ultrasound (PDUS), demonstrated hypertrophy of the lymph node cortex, in addition to power Doppler signal amplification in cortical and hilar regions likely indicating increased flow.…”
Section: Lymphatics and Rheumatoid Arthritismentioning
confidence: 99%
“…Importantly, these findings reversed with treatment ( 41 ). At the same time, low PDUS signal at baseline despite active arthritis, likely representing a collapsed lymph node, predicts poor clinical response to therapy ( 40 ). Similarly, in a pilot study using contrast enhanced MRI (CE-MRI) to monitor LN size before and after treatment with Certolizumab in RA patients, there was an inverse correlation between the extent of treatment-related pain relief and decrease in LN size.…”
Section: Lymphatics and Rheumatoid Arthritismentioning
confidence: 99%